A case study of state-corporate crime: Crown Resorts. Issue 1 (2nd January 2023) - Crofts, Penny; van Rijswijk, Honni
ABSTRACT: The concept of state-corporate crime has emerged in criminological discourse to explain the nexus of political and economic decision-making by states and corporations, and the ways this cooperation can have socially injurious impacts (Michalowski, R. J., & Kramer, R. C. [2006]. The critique of power. In R. J. Michalowski & R. C. Kramer (Eds.), State-corporate crime . New Brunswick: Rutgers, p. 15). This 'cooperation' can include corporations engaging in illegality with the tacit approval of state organisations, states failing to prevent crime, and even states colluding with corporate illegality. In this article, we use state-corporate crime theory to situate the recent wrongdoing at Crown Resorts (henceforth 'Crown'). We explain how this wrongdoing emerged within a politico-economic environment of neo-liberalism, particularly through the recent deregulation of casinos in New South Wales (NSW). We argue that the organisational decisions within Crown that breached laws and caused harms are best understood as a case of state-corporate crime.